Count your chickens after they are hatched! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Controlling Newcastle Disease in Village Chickens: A Field Manual R Alders & P Spradbrow, (ACIAR), Monographs Series 82, 2001. 112 pp. ISBN 1 86320 307 9 $AUD 25 Euro 14.15 This publication is also downloadable from: www.aciar.gov.au/publications/